IMPLEMENTASI BAGI HASIL PADA PRODUK DEPOSITO MUDHARABAH DI KSPPS BMT HALAQOH NGAWI - ciptia khoirulina; Zuhar Anwari Walid (Fakultas Ekonomi Bisnis Islam, 2022)
BMT (Baitul Mal Wat Tamwil) is a financial inclusion institution that runs a business based on sharia principles. This institution uses a profit-sharing system for several savings and financing products. There are no absolute provisions that must be obeyed by the institution, both from the Al-Qur'an-Hadith and the Law. So that all institutions are free to apply a portion of profit sharing to their business. At KSPPS BMT Halaqoh Ngawi the profit-sharing system is applied to one of its superior products, namely Mudharabah Deposits. This study aims to find out the profit-sharing system for mudharabah deposit products that are applied at KSPPS BMT Halaqoh Ngawi. The research method used in this study is a qualitative descriptive research method, using data collection techniques through interviews and documentation. The results of the study show that the deposit products at KSPPS BMT Halaqoh Ngawi use a mudharabah mutlaqoh contract. While the profit-sharing system mechanism at KSPPS BMT Halaqoh Ngawi is calculated based on the revenue-sharing method. The determination of the profit-sharing portion for each customer is based on the percentage of funds stored in the BMT according to the time period agreed upon at the beginning. For the profit sharing, it is adjusted from the acquisition of BMT income at the end of the month with the following conditions: for a 3-month term, a 30% ratio, a 6-month term, a 35% ratio, and a 12-month term, a 40% ratio. Meanwhile, the losses are borne by both parties.